Effects of Hsa-miR-4741/LILRB2 on Senescence of Nucleus Pulposus Cells and Their Prognostic Values in Lumbar Disc Herniation - Zhendong He; Nan Zheng; Xiu-Quan Guo; Gang-Gang Wang; Mingjian Lin (Journal of Investigative Surgery)
Background The incidence of lumbar disk herniation (LDH) is usually caused by lumbar disk degeneration. Surgery is a common treatment strategy for LDH, but it can recur, resulting in recurrent disk herniation (RDH).Purpose To explore the predictive value of hsa-miR-4741 and LILRB2 in the prognosis of LDH surgery and the mechanism of nucleus pulposus senescence.Method The ROC curves of RDH based on hsa-miR-4741 and LILRB2 were constructed to evaluate their predictive values in the prognosis of LDH surgery. Human nucleus pulposus cells (NPC) was treated by TNF-α to construct a cell senescence model, studying the senescence mechanism. Oxidative stress and senescence markers were detected after overexpression of hsa-miR-4741 and LILRB2 to evaluate their effects on the senescence of NPC. Dual luciferase assay and the transfection of hsa-miR-4741 mimics or inhibitor were used to investigate the targeted regulation of it to LILRB2.Results The combination of hsa-miR-4741 and LILRB2 showed higher accuracy in predicting the outcome of RDH (AUC = 0.9367), compared with a single molecule. Overexpression of hsa-miR-4741 enhanced TNF-α-induced oxidative stress and senescence, while LILRB2 overexpression had the opposite effect. Hsa-miR-4741 mimics attenuated the luciferase activity of NPC transfected with wt-LILRB2 vector and significantly down-regulated LILRB2 expression. In addition, the antioxidant NAC reversed the promotion of hsa-miR-4741 on NPC senescence.Conclusion The combination of hsa-miR-4741 and LILRB2 was a good predictor of LDH prognosis. Hsa-miR-4741 promoted oxidative stress-induced NPC senescence by negatively regulating LILRB2.